2019
DOI: 10.1093/ajcn/nqz088
|View full text |Cite
|
Sign up to set email alerts
|

Whole egg consumption compared with yolk-free egg increases the cholesterol efflux capacity of high-density lipoproteins in overweight, postmenopausal women

Abstract: Background Postmenopausal women are at higher risk for cardiovascular disease (CVD) than their younger counterparts. HDL cholesterol is a biomarker for CVD risk, but the function of HDL may be more important than HDL cholesterol in deciphering disease risk. Although diet continues to be a cornerstone of treatment and prevention of CVD, little is known about how diet affects the functionality of HDL. Objectives The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Virgin olive oil and whole grains were independently associated with increased cholesterol efflux capacity, nuts and legumes were independently associated with increased PON1 antioxidant activity, and fish consumption was associated with increased PON1 and decreased CETP activity. This supports the limited existing data of other food interventions (virgin olive oil, lycopene-rich diet, nuts and eggs) within a healthy diet that have been shown to increase HDL functionality [78,79,80,81,82].…”
Section: Potential Impact Of Dietary Patterns On Hdl Functional Chsupporting
confidence: 84%
“…Virgin olive oil and whole grains were independently associated with increased cholesterol efflux capacity, nuts and legumes were independently associated with increased PON1 antioxidant activity, and fish consumption was associated with increased PON1 and decreased CETP activity. This supports the limited existing data of other food interventions (virgin olive oil, lycopene-rich diet, nuts and eggs) within a healthy diet that have been shown to increase HDL functionality [78,79,80,81,82].…”
Section: Potential Impact Of Dietary Patterns On Hdl Functional Chsupporting
confidence: 84%
“…A study done by Andersen et al reported the PL, CE and free cholesterol proportion to be 46.0, 40.4, and 5.1 % (wt), respectively, in human subjects with MetS, and Camont et al reported the three major HDL lipid classes in similar proportions(Camont et al 2013). A study done by Sawrey-Kubicek et al found reported more PC (36.3%), TG (13.9%) and SM (8.5%), and less CE (25.9%) in postmenopausal women(Sawrey-Kubicek et al 2019). HDL lipidome composition was also reviewed byKontush et al,…”
mentioning
confidence: 96%
“…Eggs are rich in cholesterol, approximately 213 mg per egg, mainly in the yolk [ 50 ]. Clinical studies have shown that more cholesterol was detected in blood samples from women consuming whole eggs compared to a yolk-free diet [ 51 ]. High cholesterol levels make some people tend to limit the consumption of eggs, particularly yolks.…”
Section: Discussionmentioning
confidence: 99%